2018
DOI: 10.1200/jco.2017.76.1742
|View full text |Cite
|
Sign up to set email alerts
|

Pomalidomide Plus Low-Dose Dexamethasone in Patients With Relapsed/Refractory Multiple Myeloma and Renal Impairment: Results From a Phase II Trial

Abstract: Purpose Renal impairment (RI) limits treatment options in patients with relapsed/refractory multiple myeloma (RRMM). Here, we prospectively studied pomalidomide plus low-dose dexamethasone (LoDEX) in patients with RRMM and moderate or severe RI, including those receiving hemodialysis. Patients and Methods MM-013, a noncomparative, European phase II trial, enrolled three patient cohorts: moderate RI (cohort A; estimated glomerular filtration rate, 30 to < 45 mL/min/1.73 m); severe RI (cohort B; estimated glomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 28 publications
(15 reference statements)
1
45
1
1
Order By: Relevance
“…However, there are very few studies focused on the treatment of MM patients who progress to end stage renal disease and require dialysis (Chanan‐Khan et al , ; de la Rubia et al , ). Recently, results from a phase II clinical trial with pomalidomide and dexamethasone in patients with RI have been reported, with a PFS of 2·4 months in the cohort of patients requiring dialysis (Dimopoulos et al , ). Daratumumab data in patients with end‐stage RI requiring dialysis are based only on isolated case reports (Rocchi et al , ) and, to the best of our knowledge, our study is the first one to analyse the safety and efficacy of single‐agent daratumumab in patients with end‐stage renal disease.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are very few studies focused on the treatment of MM patients who progress to end stage renal disease and require dialysis (Chanan‐Khan et al , ; de la Rubia et al , ). Recently, results from a phase II clinical trial with pomalidomide and dexamethasone in patients with RI have been reported, with a PFS of 2·4 months in the cohort of patients requiring dialysis (Dimopoulos et al , ). Daratumumab data in patients with end‐stage RI requiring dialysis are based only on isolated case reports (Rocchi et al , ) and, to the best of our knowledge, our study is the first one to analyse the safety and efficacy of single‐agent daratumumab in patients with end‐stage renal disease.…”
Section: Resultsmentioning
confidence: 99%
“…Although prospective data to define optimal dosing are often lacking, pomalidomide has been studied in patients with relapsed myeloma in 3 different categories of renal insufficiency (eGFR 30-40 mL/min/1.73 m 2 , eGFR ,30 mL/min/1.73 m 2 , and those requiring dialysis), and full-dose pomalidomide of 4 mg/d was found to be safe in all 3 groups. 51 High-dose chemotherapy and autologous stem cell transplantation can be safely performed in patients with renal insufficiency, including those on dialysis. Conditioning with reduced-dose melphalan has outcomes comparable to standard-dose melphalan and should be considered in those who are otherwise eligible for the procedure.…”
Section: Myeloma Therapymentioning
confidence: 99%
“…LEN requires dose modification according to renal function. However, POM is indicated and is efficacious and safe even in patients with severe renal impairment (21). Maciocia et al (13) reported no significant difference in response, survival, or tolerability by renal function.…”
Section: Grade 3/4 All Grades ---------------------------------------mentioning
confidence: 99%